Using phenocams to monitor our changing Earth: toward a global phenocam network. Issue 2 (1st March 2016) - Brown, Tim B; Hultine, Kevin R; Steltzer, Heidi; Denny, Ellen G; Denslow, Michael W; Granados, Joel; Henderson, Sandra; Moore, David; Nagai, Shin; SanClements, Michael; Sánchez‐Azofeifa, Arturo; Sonnentag, Oliver; et al.
Abstract : Rapid changes to the biosphere are altering ecological processes worldwide. Developing informed policies for mitigating the impacts of environmental change requires an exponential increase in the quantity, diversity, and resolution of field‐collected data, which, in turn, necessitates greater reliance on innovative technologies to monitor ecological processes across local to global scales. Automated digital time‐lapse cameras – "phenocams" – can monitor vegetation status and environmental changes over long periods of time. Phenocams are ideal for documenting changes in phenology, snow cover, fire frequency, and other disturbance events. However, effective monitoring of global environmental change with phenocams requires adoption of data standards. New continental‐scale ecological research networks, such as the US National Ecological Observatory Network (NEON) and the European Union's Integrated Carbon Observation System (ICOS), can serve as templates for developing rigorous data standards and extending the utility of phenocam data through standardized ground‐truthing. Open‐source tools for analysis, visualization, and collaboration will make phenocam data more widely usable.